Pentingnya Karakter Kepemimpinan Kristen Berdasarkan 2 Timotius dalam Pelayanan Gerejawi Masa Kini - Lience Ritha Lontoh; Soeliasih; Rodianus (Sekolah Tinggi Teologi Borneo, 2022)
Abstract: Christian leadership is very attached to its character. This is the most important thing if youare to be an effective Christian leader. Someone who takes on the role of a Christian leader must be amodel or set an example for his followers. The method used in this study is descriptive qualitative, inwhich the problem of the decline in leadership character becomes the object of research. Someindicators of leaders who can be role models according to Paul in this letter are: 1) Spiritual LeadersWho Have Courageous Spirit. 2) Spiritual Leaders Who Are Willing to Suffer Without Shame. 3)Spiritual Leaders Who Have Exemplary Behavior. 4) Leaders Who Are Ready to Fight. 5) RuleabidingLeaders. 6) Diligent Leader With Patience. 7) Leaders Who Keep Trying Diligently. 8) LeadersWho Are Ready to Serve. 9) Leaders Who Live Holy. From the results of the discussion on the ninecharacteristics of leaders, it can be concluded that the qualifications of a Christian leader in 2 Timothyare very relevant and important for every church leader or spiritual leader today. This qualification isrelevant and important because nowadays it is felt that many spiritual leaders are starting to losetheir leadership character as taught by Paul in the letter 2 Timothy. The church will grow well notonly in terms of quantity but more importantly the quality of the congregation's faith will grow moreif the spiritual leader has good leadership character.Keywords: leadership; character; spiritual leaderAbstrak: Kepemimpinan Kristen sangat melekat dengan karakternya. Ini merupakan hal yang palingpenting jika hendak menjadi pemimpin Kristen yang efektif. Seseorang yang mengambil peransebagai pemimpin Kristen, harus menjadi model atau memberi teladan bagi para pengikutnya.Metode yang digunakan dalam kajian ini adalah deskriptif kualitatif, di mana persoalan kemerosotankarakter kepemimpinan menjadi obyek penelitian. Beberapa indikator pemimpin yang dapat menjaditeladan menurut Paulus dalam surat ini adalah: 1) Pemimpin Rohani Yang memiliki Semangat PenuhKeberanian. 2) Pemimpin Rohani Yang Rela Menderita Tanpa Malu. 3) Pemimpin Rohani YangMemiliki Teladan Dalam Bersikap. 4) Pemimpin Yang Siap Berjuang. 5) Pemimpin Yang TaatPeraturan. 6) Pemimpin Yang Tekun Dengan Penuh Kesabaran. 7) Pemimpin Yang Terus BerusahaDengan Gigih. 8) Pemimpin Yang Siap Melayani. 9) Pemimpin Yang Hidup Suci. Dari hasilpembahasan tentang kesembilan karakter pemimpin maka dapat disimpulkan bahwa kualifikasiseorang pemimpin Kristen di dalam 2 Timotius sangatlah relevan dan penting bagi setiap pemimpingereja atau pemimpin rohani masa kini. Kualifikasi tersebut relevan dan penting dikarena pada masakini dirasakan bahwa banyak para pemimpin rohani yang mulai kehilangan karakter kepemimpinannyasebagaimana yang diajarkan oleh Paulus di dalam surat 2 Timotius. Gereja akan bertumbuhdengan baik tidak hanya sebatas kuantitas tetapi terlebih penting kualitas iman jemaat akan semakinbertumbuh jika pemimpin rohani memiliki karakter kepemimpinan yang baik.Kata kunci: kepemimpinan; karakter; pemimpin rohani